Effect of a cluster on gas–solid drag from lattice Boltzmann simulations - Utikar, Ranjeet; Tade, Moses; Evans, G.; Shah, Milinkumar (Pergamon, 2013)
Fast fluidization of fine particles leads to formation of particle clusters, which significantly affects the drag force between the phases. Existing gas–solid drag models, both empirical and theoretical, do not account for the effect of the clusters on the drag force, and as a result, the computational studies using them are unable to capture the inherent heterogeneity of fast fluidization beds. The limitation of the current drag models is generally attributed to poor understanding of the effect of the clusters. In this study, the effect of a single cluster on the drag force has been investigated by conducting lattice Boltzmann simulations of gas–particle flow under a wide range of the overall voidage and particle Reynolds numbers. It was observed that simulations with the particles in a cluster configuration gave considerably lower drag than those with particles in a random arrangement. Furthermore, for the cluster voidage between maximum to 0.7, a significant drag reduction was observed when the inter-particle distances within a cluster was decreased. The simulations with a constant cluster voidage of 0.7 showed that the drag force decreased on decreasing the overall voidage from the maximum voidage to approximately 0.96; however any further decrease in the overall voidage caused a steep increase in the drag force. The results of this study are important in quantifying the drag reduction due to the formation of clusters.